INTEGRASI PRINSIP SYARIAH DALAM PENGELOLAAN SUMBER DAYA: STUDI KRITIS TERHADAP KEBIJAKAN PEMERINTAH DAERAH - Wisesha, Pramudya (Jurnal GeoCivic, 2024)
This study critically examines the integration of Sharia principles into local government policies for managing natural resources (NRM) in Indonesia. The wealth of natural resources, including forests, minerals, and marine ecosystems, presents both opportunities and challenges in achieving sustainability and social justice. Sharia principles emphasize justice, social responsibility, and the prohibition of excessive exploitation, providing a normative framework aligned with Indonesia's constitutional mandate to utilize natural resources for the collective welfare.Using a qualitative and literature-based methodology, the research analyzes the application of Sharia principles in NRM policies, such as community-based forest management and environmentally sustainable technologies in the mining and fisheries sectors. Findings reveal that these approaches can balance economic benefits with ecological preservation, yet challenges persist. Limited public participation, inadequate coordination among government agencies, and a lack of transparency and accountability hinder effective implementation.To address these issues, the study recommends regulatory reforms to incorporate Sharia principles, enhanced community capacity-building programs, and multi-stakeholder collaborations. The integration of Sharia values into NRM policies is proposed as a pathway to achieving more equitable and sustainable resource management, ensuring benefits for present and future generations while upholding environmental stewardship.